Study on the Dynamic Properties of Nitrile-Butadiene Rubber/Hindered Phenol Mixtures by Molecular Dynamics Simulation - Song, Meng; Zhao, Xiuying; Qiao, Bo; Zou, Hua; Wu, Sizhu (Asian Journal of Chemistry, 2013)
This paper reports the experimental and molecular simulation results of damping materials composed of nitrile-butadiene rubber (NBR) mixed with different hindered phenol (AO-80) mass ratios. The aim of this study was to determine how these AO-80 small molecules enhanced the damping behaviour of rubber mixtures from a microstructural point of view. Hydrogen bonds were formed between the AO-80 small molecules and nitrile-butadiene rubber polymer chains. Compared to the other ratios, the NBR/AO-80 mixtures with a blending ratio of 100/68 had the highest number of hydrogen bonds, resulting in the maximum loss factor and highest modulus. Possible microscopic mechanisms responsible for the enhanced damping performance of the NBR/AO-80 materials were examined by a molecular simulation.